STUDY OF THE TAXPAYERS’ COMPLIANCE IN BANKING INDUSTRIES IN SURABAYA - Kautzar Riza Salman; Mochammad Farid (Journal of Economics, Business, and Accountancy Ventura, 2010)
This research provides an empirical evidence of the influence of tax payers’ environment toward their compliance. In this research, the tax payers’ environment covers tax regulation, tax policy, tax administration, and tax services. It is a survey research by using questionnaire as the instrument. The samples used in this research include 40 regional offices or main branches of the banks associated within Perbanas (The Association of Commercial Banks) in Surabaya. They are the heads of the banks in regional offices, the heads of main branch offices, managers,supervisors or sub divisions dealing with the companies’ tax. All the respondents are by proxy on the behalf of the offices where they work. The findings are as follows: (1) tax regulation does not influence significantly toward the tax payers’ compliance; (1) the tax policy influences significantly the tax payers’ compliance; (3) the tax administration does not influence significantly toward the tax payers’ compliance; (4) the tax services does not influence significantly the tax payers’ compliance. Based on the results above, it can be concluded that the constructs of tax policy have significant influence on the tax payers’ compliance. In addition, it also shows that the constructs of tax regulation, tax administration, and tax services do not have significant influence on the tax payers’ compliance.